MicroRNAs: Key regulators of endothelial progenitor cell functions - Qu, Kai; Wang, Zuo; Lin, Xiao-long; Zhang, Kai; He, Xing-lan; Zhang, Hai (Clinica chimica acta, 2015)
Development of cardiovascular diseases mobilises endothelial progenitor cells (EPCs) from the bone marrow to participate in vascular repair and formation of new blood vessels under both pathological and physiological conditions. Therefore, EPCs show great potential for therapeutic applications; however, the phenotypic and functional characterisation of EPCs is still difficult because controversies exist regarding their accurate definition. Growing studies have shown modest clinical benefits of EPCs; however, it is necessary to better understand the regulation of EPC functions. MicroRNAs are small, non-coding, single-stranded RNAs with regulatory activities. Results of some recent studies have found that microRNAs play an important role in regulating EPC functions. In this review, we will summarise the results of some recent studies to provide an integral picture of the role of microRNAs in the regulation of EPC functions and will discuss the therapeutic applications and the new research direction. •MicroRNAs regulate the proliferation, differentiation and senescence of EPCs.•MicroRNAs regulate the mobilisation and migration of EPCs.•MicroRNAs regulate the ability of tubule structure formation of EPCs and EPCs-inducted angiogenesis.•MicroRNAs regulate other function of EPCs.•Related signalling pathways